Preparation and characterization of a novel antimicrobial film dressing for wound healing application - Melissa Marques Gonçalves; Jaqueline Carneiro; Barbara Justus; Joel Toribio Espinoza; Jane Manfron Budel; Paulo Vitor Farago; Josiane Padilha de Paula (Universidade de São Paulo, 2021)
Antibacterial activity and good mechanical properties are some of the characteristics required for an appropriate film dressing. A novel polymer blend was developed for wound healing application. Twenty-four formulations using the polymers chitosan, poly(vinyl alcohol) and/or ɛ-Polylysine and the plasticizer glycerol were designed using factorial design and then the films were prepared by the casting/solvent evaporation method. Seventeen films were obtained among the twenty-four proposed formulations that were characterized by Field Emission Scanning Electron Microscopy (FE-SEM) and Fourier Transform Infrared Spectroscopy (FTIR). Mechanical properties, such as tensile strength (σ), elongation at break (ɛ) and Young's modulus (Y) as well as antibacterial properties were determined. The best candidate was then further analyzed with regard to porosity, Water Vapor Transmission Rate (WVTR), swelling and cytotoxicity experiments. The results showed a film with semi-occlusive characteristics, good mechanical properties and no toxic. Incorporation of ɛ-Polylysine increased antibacterial activity against gram-negative (Escherichia coli) and gram-positive (Staphylococcus aureus) bacteria.